2006
DOI: 10.1016/j.febslet.2006.05.006
|View full text |Cite
|
Sign up to set email alerts
|

CYP4A11 is repressed by retinoic acid in human liver cells

Abstract: CYP4A11, the major fatty acid x-hydroxylase in human liver is involved in the balance of lipids, but its role and regulation are both poorly understood. We studied the effects of retinoids on the regulation of CYP4A11 in the human hepatoma cell line HepaRG. Treatment of HepaRG cells with all-trans-retinoic acid resulted in a strong decrease in CYP4A11 gene expression and apoprotein content and, furthermore, was associated with a 50% decrease in the microsomal lauric acid hydroxylation activity. Such a strong s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 43 publications
1
13
0
Order By: Relevance
“…Likewise, we observed that CYP4A11 expression was down-regulated in DMSO-treated cells. This supports the well established differential regulation of the human CYP4A genes, especially CYP4A11, which was shown to be regulated by retinoic acid, bezafibrate, and dexamethasone in human (Savas et al, 2003;Antoun et al, 2006).…”
Section: Steps Of Differentiationsupporting
confidence: 85%
“…Likewise, we observed that CYP4A11 expression was down-regulated in DMSO-treated cells. This supports the well established differential regulation of the human CYP4A genes, especially CYP4A11, which was shown to be regulated by retinoic acid, bezafibrate, and dexamethasone in human (Savas et al, 2003;Antoun et al, 2006).…”
Section: Steps Of Differentiationsupporting
confidence: 85%
“…S3) (44-46). On the other hand, ATRA has been shown to be a strong inducer of CYP4Fs (32,33), while it suppressed expression of CYP4A11 (34). Upon treatment with ATRA, we observed a more than 2-fold increase in the downstream metabolites, suggesting that CYP4F rather than CYP4A enzymes are involved.…”
Section: The Downstream Metabolism Of 1-deoxyso Is Mediated By Cyp4f mentioning
confidence: 55%
“…As HET0016 inhibits both CYP4A and CYP4F enzymes, we treated cells with all-trans retinoic acid (ATRA; 20 M), which preferentially induces the expression of CYP4F genes (32)(33)(34). ATRA treatment significantly increased all the d3-deoxySL downstream metabolites.…”
Section: The Metabolic Conversion Of 1-deoxysls Is Slow Compared Withmentioning
confidence: 99%
“…After 12 days, the medium was supplemented at first with 1% DMSO and then with 2% DMSO until the 24th day, when the different treatments were applied, according to previous reports (26).…”
Section: Cell Culturementioning
confidence: 99%
“…Total RNA was extracted using the ABI Prism™ 6100 Nucleic Acid PrepStation (Applied Biosystems, Courtaboeuf, France) as described (26). The integrity of total RNA was checked on an Agilent 2100 Bioanalyser using the RNA 6000 Nano LabChip kit (Agilent Technologies, Palo Alto, CA).…”
Section: Rna Extraction and Quality Controlmentioning
confidence: 99%